INTERAKSI AKTOR DALAM PENYELESAIAN KONFLIK TANAH ULAYAT DI KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM PROVINSI SUMATERA BARAT TAHUN 2008- 2012 - Ria Suryani; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is motivated by the conflict between PT Mutiara Agam with Indigenous peoples Nagari Tanjung Manggopoh which takes place in a long duration. The conflict between PT Mutiara Agam with this community due to customary by people Nagari Tanjung Manggopoh demanding PT Mutiara Agam according of land of 2500 ha of communal land they are located in villages Tiku V Jorong. This study aims to determine how the portrait of conflict management is done through the interaction of the actors. This study uses a qualitative assessment of descriptive data. In the data collection researchers use interviewing techniques and documentation. By using key informants and documents as sources of information.The results showed the communal land conflicts Pasukuan Tanjung Manggopoh with PT. Agam pearl has been going in a long duration. The conflict due to the protracted conflict management failed to reach a consensus as its platform for true peace. The fundamental difference between customary law with formal law, the difference between the oral tradition to written tradition are strong reasons to see the failure of communal land conflict management. Broadly speaking portraits of communal land conflicts pesukuan Nagari Tanjung Manggopoh with PT Mutiara Agam has a complex actor. Many actors below the surface of the main actors are reproducing new conflict as a result of major conflicts protracted. The dynamics of long duration, and complexity of the actors makes the conflict has shifted the issue and form a layered structure of conflict. The issue was originally a conflict because identity is threatened, shifted into conflicts of interest of social, economic, and political of all actors.Keywords: Actor Interactions, Conflict, Communal Land